Effect of Natural Chinese Herbal Supplements (TCMF4) on Lactation Performance and Serum Biomarkers in Peripartal Dairy Cows - Cui, Yizhe; Shan, Zhuorui; Hou, Lintong; Wang, Qiuju; Loor, Juan J.; Xu, Chuang (Frontiers in Veterinary Science, 2022)
This study examined the effect of mixed medicinal herbs from China in the ground form on milk yield and various blood metabolites before and after parturition in Holstein cows. Crushed Agastache rugosus, Scutellaria barbata, Pericarpium citri reticulate, and Radix glycyrrhizae were used to develop TCMF4. Thirty-two Chinese Holstein cows were randomly divided into a control group or groups receiving 0.1, 0.3, or 0.5 kg TCMF4/cow/d from −7 through 21 d relative to parturition. Blood samples for serum isolation were collected at −7, −1, 1, 7, 14, and 21 d relative to parturition and used to measure glucose, β-hydroxybutyric acid (BHBA), total protein, albumin, globulin, and alkaline phosphatase. Milk production was recorded daily for the first 21 d postpartum, and composition was analyzed at 7, 14, and 21 d. Data were analyzed using a one-way analysis of variance (ANOVA) for multiple comparisons. The average milk production during the first 21-d postpartum was 28.7 ± 6.9, 27.2 ± 7.1, 31.2 ± 6.8, and 38.5 ± 6.1 kg/d for control group and groups receiving 0.1, 0.3, or 0.5 kg TCMF4. Thus, average daily milk production increased between 9 to 34% by supplementation with TCMF4 compared with the control group. Compared with the control group, in the middle dose group, milk concentrations of lactose and total protein decreased by 21 and 19%, respectively, at d 7 around parturition, while total solids increased by 23% at d 21 in the high-dose group. Furthermore, compared with the control group, serum BHBA decreased by 50 and 20% at d −1 and 21 around parturition in the high-dose group. Overall, TCMF4 supplementation improved dry matter intake (DMI) and milk production of dairy cows during the periparturient period without adverse effects on liver function, and plasma BHBA concentrations of dairy cows tended to decrease when dietary TCMF4 increased, which suggested that TCMF4 might be used as potential additives in dairy cows to improve production performance.